Coordinated microRNA/mRNA Expression Profiles Reveal Unique Skin Color Regulatory Mechanisms in Chinese Giant Salamander (Andrias davidianus) - Yanjie Guo; Weini Wu; Xueyi Yang (Animals, 2023)
The Chinese giant salamander (Andrias davidianus) has been increasingly popular in the aquaculture market in China in recent years. In the breeding process of Andrias davidianus, we found that some albino individuals were extremely rare and could not be inherited stably, which severely limits their commercialization in the aquaculture market. In this study, we performed transcriptome and small RNA (sRNA) sequencing analyses in the skin samples of wild-type (WT) and albino (AL) Andrias davidianus. In total, among 5517 differentially expressed genes (DEGs), 2911 DEGs were down-regulated in AL, including almost all the key genes involved in melanin formation. A total of 25 miRNAs were differentially expressed in AL compared to WT, of which 17 were up-regulated. Through the integrated analysis, no intersection was found between the target genes of the differentially expressed miRNAs and the key genes for melanin formation. Gene Ontology (GO) and KEGG pathway analyses on DEGs showed that these genes involved multiple processes relevant to melanin synthesis and the key signal pathway MAPK. Interestingly, the transcription factors SOX10 and PAX3 and the Wnt signaling pathway that play a key role in other species were not included, while the other two transcription factors in the SOX family, SOX21 and SOX7, were included. After analyzing the key genes for melanin formation, it was interesting to note an alternative splicing form of the MITF in WT and a critical mutation of the SLC24A5 gene in AL, which might be the main reason for the skin color change of Andrias davidianus. The results contributed to understanding the molecular mechanism of skin pigmentation in Andrias davidianus and accelerating the acquisition process of individuals with specific body colors by genetic means.